2018
DOI: 10.5433/1679-0359.2018v39n3p1211
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the scale of production on the cost-effectiveness of milk production systems belonging to the “Balde Cheio” program

Abstract: This study investigates the cost-effectiveness of 20 demonstration units (DUs) belonging to the "Balde Cheio" program. The units in question are from the state of Rio de Janeiro, Brazil, dating from January to December 2011, and are sorted according to the scale of production (small, medium and large). The data were analyzed using Predictive Analytical software (PASW) 18.0. The scale of production influenced the total cost of milk production, and therefore profitability and cost-effectiveness. The largescale s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 3 publications
2
11
1
3
Order By: Relevance
“…This spreadsheet included the two production cost structures (i.e., total production cost), which consisted of fixed and variable operating costs, both used by Lopes et al (2019) and Pelegrini et al (2019). The linear depreciation method was used in this study (Moraes et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This spreadsheet included the two production cost structures (i.e., total production cost), which consisted of fixed and variable operating costs, both used by Lopes et al (2019) and Pelegrini et al (2019). The linear depreciation method was used in this study (Moraes et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…It occurred because of an increase in production scale due to improved use of biogas. Moraes et al (2018) observed that production scale influenced total operating production cost and hence profitability. The authors attributed such result to a physical structure optimization in the company since total operating cost per unit was reduced by increasing production scale up to certain levels.…”
Section: Specificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The data were recorded in a spreadsheet with two production cost structures, namely, Total Production Cost, which involves fixed and variable costs, and Operating Costs, both used by Lopes et al (2019) and Pelegrini et al (2019). In this study, the straight-line depreciation method used by Moraes et al (2018) was adopted. For the depreciation of machinery and implements used to stir the sand, an apportionment criterion was employed, considering only 12% of the value; the remainder (88%) was computed for the milk production cost center.…”
Section: Methodsmentioning
confidence: 99%
“…This spreadsheet included the two production cost structures, that is, total costs, related to the fixed and variable costs, and operating costs, both used by Lopes et al (2019) and Pelegrini et al (2019). The straightline depreciation method was used in this study (Moraes et al, 2018).…”
Section: Methodsmentioning
confidence: 99%